The Legal Protection for Buyers of Land with Letter C Status in the Presence Land Deed Making Officer (PPAT) - Lestari, Yulia; Hasana, Dahniarti (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The purpose of this research is to analyze: 1) The process of making a deed of sale and purchase of land with Letter C status by the Land Deed Making Officer (PPAT). 2) Legal protection for the buyer of the sale and purchase of land that is still in Letter C status before the Land Deed Maker Official (PPAT). The approach method used in discussing this research problem was a sociological juridical approach. The specification of the research used is descriptive analytical research. The results of the study concluded: 1) The process of making a land sale and purchase deed with Letter C status by the Land Deed Maker Official (PPAT) is actually not much different from the sale and purchase of land that has been certified. However, in making a deed of sale and purchase of land with letter c status, a photocopy of Letter C must be attached, a quote from Letter C, a legalized statement of control and ownership of the land and explain that the person concerned controls the plot of land. After all the required documents have been fulfilled by the parties, the sale and purchase of land can be carried out before the PPAT. 2) Legal protection for the buyer of the sale and purchase of land that is still in Letter C status before the Land Deed Making Officer (PPAT) can be realized by making a Sale and Purchase Deed and the issuance of a certificate of land rights on behalf of the buyer. So that based on jurisprudence the buyer's land rights can be protected. These deed of sale and purchase and land certificates are a form of repressive protection.